Reading Carol Ann Duffy’s politics through unnatural ecopoetics - Abdul Kidhim Mhana, Zainab; Talif, Rosli; Zainal, Zainor Izat; Abdul Hadi, Ikhlas (Universiti Kebangsaan Malaysia Press, 2019)
Carol Ann Duffy is one of the most notable poets in contemporary English poetry. In accordance with her poetic dexterity, she was appointed as Great Britain’s Poet Laureate in 2009. This study deals with Duffy’s “Politics,” which was introduced inThe Bees (2011), her first collection published after having been named Poet Laureate. In this poem, the poet tackled natural and unnatural imagery resultant from diverse experiences. This study proposes that the material environment surrounding Carol Ann Duffy is intertwined with her nonmaterial environment in “Politics.” This argument runs parallel with the concept of unnatural ecopoetics, which is considered to be a new direction in ecopoetics in examining contemporary poetry.The current study argues that the poet’s ideology after becoming poet laureate and also her experience as a Scottish, feminist, bisexual poet have all together configured a kind of nonmaterial environment intertwined with the material world or nature in the textual space through “Politics”. This assumption is not far from Sarah Nolan’s concept of Unnatural Ecopoetics in her book Unnatural Ecopoetics: Unlikely Spaces of Contemporary Poetry (2017). So, this study is conducted in the light of Nolan’s concept, which denotes the relations between the human, natural, and unnatural environments and the language in the poetic text. Accordingly, more focus will be on the poet’s experiences, memories, ideology, and feelings which inspired her to symbolize nature in another dimension in “Politics” as an unnatural ecopoetics poem.